2018
DOI: 10.3389/fpsyg.2017.02271
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Spatial Attentional Allocation by Computer-Based Cognitive Training during Lacrosse Shooting Performance

Abstract: It has been reported that repetitive execution of a stimulus–response compatibility (SRC) task attenuates the interference effect of a choice reaction time task, known as a Simon task. We investigated whether attentional control, enhanced by repetitive execution of an SRC task, would reduce the interference effect of a Simon task and could be transferred to lacrosse shooting skills, increasing the likelihood that players would shoot in the direction opposite to the goalie’s initial movement. Female lacrosse pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 30 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…In a previous study, we clearly showed that the modulation of the spatial attentional allocation induced by 1,800 repetitions of the Type 2 task could transfer to dynamic movements, like the shooting motion in lacrosse (Hirao and Masaki, 2018). In that study, male lacrosse players who acquired a temporal representation for the spatial attentional allocation by executing a total of 1,800 trials of the Type 2 task took more shots in directions opposite to the goalie's movement.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In a previous study, we clearly showed that the modulation of the spatial attentional allocation induced by 1,800 repetitions of the Type 2 task could transfer to dynamic movements, like the shooting motion in lacrosse (Hirao and Masaki, 2018). In that study, male lacrosse players who acquired a temporal representation for the spatial attentional allocation by executing a total of 1,800 trials of the Type 2 task took more shots in directions opposite to the goalie's movement.…”
Section: Introductionmentioning
confidence: 82%
“…Previous studies have implied that the magnitude of the Simon effect can be ascribed to the age group. Participants aged 5-8 years have demonstrated a complete reversal of the Simon effect (Tagliabue et al, 2000), although participants aged 19-25 years have demonstrated a fading magnitude of the Simon effect (Tagliabue et al, 2000;Hirao and Masaki, 2018). It is reasonable to assume that the Simon effect in young adults may not be reversed because a representation of a strong link between stimuli and response locations was fully consolidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Separately, and not reviewed by Harris et al (2018) , Hirao and Masaki (2018) used the Simon Task to make those trained more able to shoot toward the opposite direction of a goal-keepers initial lateral movement. Twenty-nine lacrosse players were split into two groups, either conducting Stimulus-Response Compatibility Training, or an active control.…”
Section: Enhancing Cognition For Elite Performancementioning
confidence: 99%
“…The work of Romeas et al (2016) and Hirao and Masaki (2018) are certainly exciting, and a positive step in the right direction for investigating the potential efficacy of CT in sport via peer-reviewed controlled trials. However, given the known difficulty of achieving far transfer following CT, it is surprising that the only known studies have both provided positive effects.…”
Section: Enhancing Cognition For Elite Performancementioning
confidence: 99%